Pathways to Prosperity: Navigating Post-Stagnation Growth and Revitalizing Business; Economies; Vol. 12, iss. 3 - Spitsin V. V. Vladislav Vladimirovich; Vukovic D. B. Darko; Ryzhkova M. V. Marina Vyacheslavovna; Leonova V. A. Victoria Aleksandrovna (2024, 2024)
Title screen